Anti-microbial efficiency of nano silver–silica modified geopolymer mortar for eco-friendly green construction technology. Issue 79 (28th August 2015) - Adak, Dibyendu; Sarkar, Manas; Maiti, Moumita; Tamang, Abiral; Mandal, Saroj; Chattopadhyay, Brajadulal
<x xml:space="preserve">Abstract</x> Schematic representation of the anti-bacterial action of silver–silica modified geopolymer mortar for green construction technology.